Osteomas of the craniofacial region: A case series and review of literature - Sagar Gundewar; Deepak S. Kothari; Nitin J. Mokal; Amol Ghalme (Indian Journal of Plastic Surgery)
Objective: 0 To discuss the clinical presentation, diagnosis and management of osteomas involving the craniomaxillofacial region. Materials and Methods: This study was conducted from June 2004 to March 2012 at our institute. A total of 12 cases between the ages of 10 and 50 years were managed with surgical excision and reconstruction. The criteria used to diagnose osteoma included radiographic and clinical features and histological confirmation of the specimen. The total follow-up period ranged from 6 to 24 months. Results: Out of 12 osteomas, 10 were peripheral and 2 were centrally located. Mandible involvement was seen in six patients, four involved the orbit, one the frontal bone and one the frontal bone with the skull base. All patients undergoing excision and reconstruction had a favourable aesthetic and functional outcome. There were no recurrences and no post-operative complications. Conclusion: Osteomas affect all age groups with no sex predilection and are usually clinically asymptomatic till they become large in size. Surgical excision and appropriate reconstruction is the mainstay of management. Surgery is indicated when lesion is symptomatic or actively growing and the surgical approach for exposure of the lesion should be case specific.